2020
DOI: 10.1007/s00253-020-10800-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Ala234Asp replacement in mitochondrial branched-chain amino acid aminotransferase on the production of BCAAs and fusel alcohols in yeast

Abstract: In the yeast Saccharomyces cerevisiae, the mitochondrial branched-chain amino acid (BCAA) aminotransferase Bat1 plays an important role in the synthesis of BCAAs (valine, leucine and isoleucine). Our upcoming study [Large et al. 2020

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…These opposite phenomena are potentially caused by the functional differences between Bat1 and Bat2, such as regulation of the BAT1 and BAT2 gene expression, expression of the BAT1 and BAT2 genes in different status of cell growth or nutrients, and localization of the Bat1 and Bat2 enzymes, all of which were mentioned above (Colón et al 2011;Eden et al 1996;González et al 2017;Hammer and Avalos 2017;Kispal et al 1996;Takpho et al 2018). Our recent study also showed the relevance for the effect of intracellular BCAA contents on the production levels of fusel alcohols by using the bat1Δ strain (Koonthongkaew et al 2020). Interestingly, the differences between the localization of Bat1 and that of Bat2 were consistent with the places where BCAA biosynthesis and the Ehrlich degradation of BCAAs in cells mainly occur.…”
Section: Phenotypic Differences Related To Bat1 and Bat2supporting
confidence: 59%
See 4 more Smart Citations
“…These opposite phenomena are potentially caused by the functional differences between Bat1 and Bat2, such as regulation of the BAT1 and BAT2 gene expression, expression of the BAT1 and BAT2 genes in different status of cell growth or nutrients, and localization of the Bat1 and Bat2 enzymes, all of which were mentioned above (Colón et al 2011;Eden et al 1996;González et al 2017;Hammer and Avalos 2017;Kispal et al 1996;Takpho et al 2018). Our recent study also showed the relevance for the effect of intracellular BCAA contents on the production levels of fusel alcohols by using the bat1Δ strain (Koonthongkaew et al 2020). Interestingly, the differences between the localization of Bat1 and that of Bat2 were consistent with the places where BCAA biosynthesis and the Ehrlich degradation of BCAAs in cells mainly occur.…”
Section: Phenotypic Differences Related To Bat1 and Bat2supporting
confidence: 59%
“…Many findings concerning the physiological functions of Bat1 have been obtained from investigations performed to improve fusel alcohol production, especially with isobutanol, by utilizing yeast strains. Several studies have demonstrated an increase in the production level of isobutanol by deletion of the BAT1 gene (Park et al 2014;Hammer and Avalos 2017;Koonthongkaew et al 2020). Meanwhile, other studies have indicated a decrease (Ofuonye et al 2013) or no significant impact (Eden et al 2001;Zhang et al 2016) in isobutanol production levels by the deletion of the BAT1 gene.…”
Section: Mitochondrial Bcaa Aminotransferase (Bat1) In Yeastmentioning
confidence: 99%
See 3 more Smart Citations